2020
DOI: 10.1021/acs.jmedchem.0c00844
|View full text |Cite
|
Sign up to set email alerts
|

Saturated Hydroxy Fatty Acids Exhibit a Cell Growth Inhibitory Activity and Suppress the Cytokine-Induced β-Cell Apoptosis

Abstract: The field of bioactive lipids is ever expanding with discoveries of novel lipid molecules that promote human health. Adopting a lipidomic-assisted approach, two new families of previously unrecognized saturated hydroxy fatty acids (SHFAs), namely, hydroxystearic and hydroxypalmitic acids, consisting of isomers with the hydroxyl group at different positions, were identified in milk. Among the various regio-isomers synthesized, those carrying the hydroxyl at the 7- and 9-positions presented growth inhibitory act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(46 citation statements)
references
References 58 publications
(97 reference statements)
3
42
1
Order By: Relevance
“…As mentioned in the introduction, we have most recently studied the cell growth inhibitory activity of various HSAs and HPAs, and we have found that 7RHSA exhibited the highest potency on epithelial lung carcinoma (A549) cell line with an IC 50 value of 38 μM. 13 In the present work, we studied the effect of a number of synthesized OPAs and OSAs on the proliferation of three human cancer cell lines: epithelial lung carcinoma (A549), colorectal adenocarcinoma (Caco-2), and astrocytoma (SF268). The MTT assay was employed to assess viable cell numbers.…”
Section: ■ Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…As mentioned in the introduction, we have most recently studied the cell growth inhibitory activity of various HSAs and HPAs, and we have found that 7RHSA exhibited the highest potency on epithelial lung carcinoma (A549) cell line with an IC 50 value of 38 μM. 13 In the present work, we studied the effect of a number of synthesized OPAs and OSAs on the proliferation of three human cancer cell lines: epithelial lung carcinoma (A549), colorectal adenocarcinoma (Caco-2), and astrocytoma (SF268). The MTT assay was employed to assess viable cell numbers.…”
Section: ■ Resultsmentioning
confidence: 97%
“…Following a suspect analysis approach involving an LC-HRMS technique, we successfully identified new families of bioactive SHFAs in milk. 13 In the present work, our aim was to explore if families of SOFAs are present in human plasma and cow milk.…”
Section: ■ Resultsmentioning
confidence: 99%
See 3 more Smart Citations